Research on deformation coordination of composite metal gears in the process of cold extrusion. Issue 1 (1st September 2022) - Wang, Tao; Zhang, Yishuai; Sun, Hongxing; Wang, ZhengBing; Liu, Hua
Abstract: In order to realize lightweight manufacturing of gear parts, the cold extrusion forming process of steel-aluminum composite metal gears was studied. Using numerical simulation software Deform, the effects of five steel rings with different thicknesses on forming pressure and shapes of formed forgings were compared. The simulation results showed that final forming force of the gear was smaller and the radial deformation degree of steel ring was larger when using thinner steel ring. This radial deformation degree was characterized by height difference between the convex and the concave in steel-aluminum bonding position, and great deformation presented as obvious bimetal occlusion. The physical experiment verified numerical simulation results, and meanwhile found that the thickness of steel sleeve had an important effect on bonding tightness of steel-aluminum contact surface of formed part and the composite gear formed by thin steel ring had a gap at tooth tip between steel and aluminum. Comprehensive analysis suggested the ratio of outer diameter to inner diameter (R0/Ri) of steel sleeve reflected different deformation regularity. Consequently, the thick-walled axial compression model was used to analyze forming process of steel sleeve with high R0/Ri ratio, and the thin-walled cylindrical shell model was used to analyze forming process of steel sleeve with low R0/Ri ratio. The axial compression of thin cylindrical shell produced local buckling deformation, which led to the appearance of gaps in steel-aluminum bonding position. In order to avoid gaps in bimetal contact surface, the influence of steel ring thickness on deformation coordination of two metals should be fully considered in cold extrusion of steel-aluminum composite metal gear.